PENGARUH KOMITMEN KARIR DAN KESUKSESAN KARIR SUBJEKTIF TERHADAP KESIAPAN MENGHADAPI PERUBAHAN - Fridayanti Fridayanti (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2011)
The aim of this study is to test the influence of career commitment and subjective career success toward readiness to change. The subject of this study were 41 full time teachers who work in SMA ,which is hold the status of Pioneering International Standard-Based School and now this school is being process of change to become International Standard Based Schol. Data was collected by three measuring instruments or questionaires, namely by career commitment, subjective career success and readiness for change. Measurements were conducted using path analysis, with the assistence by software Statistical Packages for Social Science (SPSS) 17.0 for Windows. The result of this research showed that hypothesis to be tested was significan,. It means that readiness to change could be predicted by career commitment and subjective career succes, either simultaneously or partially. The amount of power influence of career commitment is 24.76 % (0.2476). Subjective Career Success toward readiness to change is 16,61% (0,166). Simultaneously, the amount of influence of career commitment and subjective career success toward readiness to change is 41,4% (0,144)